From plate to planet: culturally responsive culinary practices for health system innovation - Loy, Michelle H. (Frontiers in Nutrition, 2024)
The field of culinary medicine has gained significant attention for its potential to improve health outcomes through the integration of nutrition and medical practice. However, the cultural dimensions of this interdisciplinary field remain underexplored. Emphasizing the role of sociocultural practices, the paper highlights how culturally appreciative culinary practices can meet the sextuple aim of health care system innovation. By examining diverse cultural traditions and their contributions to culinary medicine, this review underscores the importance of culturally attuned approaches in promoting human health. The integration of cultural food wisdom into healthcare practices offers a pathway to more effective and personalized care, stronger patientprovider relationships, diversity/equity/inclusion/belonging, and sustainable food systems.